2008
DOI: 10.1590/s0100-29452008000200029
|View full text |Cite
|
Sign up to set email alerts
|

Diferenciação genética entre procedências de açaizeiro por marcadores RAPD e SSR

Abstract: RESUMO -Diferenciação genética refere-se à distribuição da variabilidade entre e dentro de populações, procedências ou outros tipos de agrupamentos. Seu conhecimento é importante para estabelecer estratégias de coleta, conservação e manejo de germoplasma de qualquer espécie. Neste trabalho, avaliou-se a diferenciação genética entre procedências de açaizeiro que compõem a coleção da Embrapa Amazônia Oriental, por meio de marcadores RAPD e SSR. Para tanto, foram utilizados DNAs de 107 acessos, representantes de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
(13 reference statements)
0
9
0
3
Order By: Relevance
“…In Euterpe edulis, there was 57.4 % of diversity within populations (Cardoso et al 2000); in M. urundeuva this value was 83.8 % (Freitas et al 2005); in Eremanthus erythropappus 79 % (Estopa et al 2006) and in one açai species of the genus Euterpe, Oliveira and Silva (2008) found a variability of 75.85 % for dominant markers, RAPD and 69.88 % for co-dominant SSR markers.…”
Section: Resultsmentioning
confidence: 99%
“…In Euterpe edulis, there was 57.4 % of diversity within populations (Cardoso et al 2000); in M. urundeuva this value was 83.8 % (Freitas et al 2005); in Eremanthus erythropappus 79 % (Estopa et al 2006) and in one açai species of the genus Euterpe, Oliveira and Silva (2008) found a variability of 75.85 % for dominant markers, RAPD and 69.88 % for co-dominant SSR markers.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, due to their high polymorphism rate, codominant inheritance and multiallelic nature, SSR markers are highly reproducibility and require small amounts of DNA (Oliveira, Pádua, Zucchi, Vencovsky, & Vieira, 2006;Oliveira & Silva, 2008). Several studies with sweet potato culture using SSR markers have observed high genetic diversity among accessions, including Veasey et al (2008) and Koussao et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Other Neotropical palm species with an allogamous habit show relatively low values for within genetic variation, such as 57.4% for E. edulis (Cardoso et al, 2000) and 75.85% for E. oleracea (Oliveira and Silva, 2008). The high differentiation between the sample places of O. mapora may be related to the limited distances covered by beetles, their natural pollinators (Kuchmeister et al, 1998;Couturier et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…However, these markers can generate enough polymorphism to estimate the levels of genetic variation in the populations evaluated. Analysis of molecular variance (AMOVA) procedure allows us to determine the distribution of genetic variation within and between different types of groups, such as natural populations, and has been substantially applied in studies of plants with dominant markers (Rodrigues et al, 2004;Oliveira and Silva, 2008;Gomes et al, 2011). Although the use of RAPD has been criticized (Jones et al, 1997), information generated by theses markers has been confirmed by other more refined techniques.…”
Section: Introductionmentioning
confidence: 99%